1991
DOI: 10.1103/physrevlett.67.739
|View full text |Cite
|
Sign up to set email alerts
|

Absence of quantum corrections to the anomalous Hall conductivity

Abstract: We discuss quantum corrections to the anomalous Hall conductivity in disordered metallic films containing magnetic moments. Within a model of skew scattering we show that Coulomb-anomaly terms vanish identically. The weak-localization contribution is cut off by the phase-breaking effect of skew scattering. In a dense system of magnetic moments, the internal magnetic field may cause a more rapid destruction of phase coherence. Our findings are in agreement with a recent experiment on ferromagnetic amorphous Fe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
38
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 12 publications
9
38
0
Order By: Relevance
“…For well-conducting samples, the behavior could be well explained by the WL theory 13,15 of the AHE in two-dimensional homogeneously disordered samples. For more resistive samples, however, noticeable deviations from the theoretical predictions were observed.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…For well-conducting samples, the behavior could be well explained by the WL theory 13,15 of the AHE in two-dimensional homogeneously disordered samples. For more resistive samples, however, noticeable deviations from the theoretical predictions were observed.…”
Section: Introductionmentioning
confidence: 81%
“…Weak localization (WL) effects were studied in Refs. 13,14,15 and it was demonstrated that WL correction to AH conductivity is nonzero 13,14,15 for skewscattering and vanishes 14,15 for side-jump mechanism. The logarithmic temperature dependence of the AH resistivity and the absence of such for the AH conductivity observed in amorphous iron films 16 were initially attributed to the Coulomb interactions 13 and later interpreted 15 in terms of the WL corrections for the side-jump mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is similar here for the quantized AHE system. In the thin film of Fe, ln T -dependence of σ xx is observed while not for σ xy [20], which is explained by the quantum Coulomb correction combined with the skew scattering mechanism [21].…”
Section: Its Hamiltonian Is Written Asmentioning
confidence: 97%
“…This experimental observation of negligible skew scattering caused by weak localization are also supported by the early theoretical work. 25,[29][30] The discrepancies and puzzlingly large n in Figs. 3(a) and (b) should be attributed to their unreasonable presupposition α 0 =α L =α p =α m , i.e.…”
mentioning
confidence: 99%